The Influence Of Work Discipline And Work Facilities On The Work Productivity Of Main PO TKM Employees - Sartika, Rahma Tri; Sutrisna, Arga; Patimah, Titin (Journal of Management, Economic, and Accounting, 2024)
PO TKM UTAMA is a company operating in the field of public transportation which was founded in 1952. The productivity of operational employees has fluctuated, decreasing and increasing productivity results. This purpuse of this study to determine the influence of work discipline and work facilities on the work productivity of PO TKM UTAMA employees. The method used was a quantitative approach with a research sample of 76 respondents from the Operational Department Employees of PO TKM UTAMA. The data used is primary data and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. The research results show that work discipline and work facilities simultaneously have a significant effect on work productivity. Partially, work discipline has a significant effect on work productivity and work facilities have a significant effect on work productivity.